Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/00005537-200408000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Skin Testing in Predicting Response to Nasal Provocation with Alternaria

Abstract: Skin testing with either epicutaneous or intradermal testing may not be an accurate or sufficient technique in the assessment of Alternaria reactivity. These results suggest that mold allergies may involve more complex immune mechanisms than simply an immunoglobulin (Ig)E mediated type I immediate hypersensitivity response alone. An alternate model for mold sensitivity, as well as modifications in testing methods, may be required in the evaluation of mold allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 8 publications
1
54
0
1
Order By: Relevance
“…In a separate study, Nelson et al, 9 evaluating timothy grass, found that a positive single intradermal skin test response in the presence of a negative SPT result did not indicate the presence of clinically significant sensitivity. The results for molds have not been as convincing, with poor sensitivity and specificity of SPT for Alternaria and modest improvement when further evaluating SPT negative tests with single intradermal tests 42 . There is controversy regarding which classes of antigens may have SPT negative results but clinically significant positive intradermal test results 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a separate study, Nelson et al, 9 evaluating timothy grass, found that a positive single intradermal skin test response in the presence of a negative SPT result did not indicate the presence of clinically significant sensitivity. The results for molds have not been as convincing, with poor sensitivity and specificity of SPT for Alternaria and modest improvement when further evaluating SPT negative tests with single intradermal tests 42 . There is controversy regarding which classes of antigens may have SPT negative results but clinically significant positive intradermal test results 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The results for molds have not been as convincing, with poor sensitivity and specificity of SPT for Alternaria and modest improvement when further evaluating SPT negative tests with single intradermal tests. 42 There is controversy regarding which classes of antigens may have SPT negative results but clinically significant positive intradermal test results. 47 More work needs to be performed to more clearly determine which antigens deserve further evaluation when SPT results are negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the general notion that the levels of IgG indicate the amount of immunologic exposure, these results suggest a direct correlation between the exposure to Alternaria antigens and the severity of the immune reaction as determined by the amount of IL-5 production. Other investigators also found an increase of nasal obstruction after challenge with Alternaria that was independent from an IgE-mediated hypersensitivity [35]. In a recent study, eosinophils from healthy people that were incubated with Alternaria and Penicillium antigens released significant amounts of eosinophil-derived neurotoxin, a marker of eosinophil degranulation [36].…”
Section: Why Do Eosinophils Exist? the Immune Response To Fungimentioning
confidence: 91%
“…Subsequently, the production of cytokines crucial to induce an eosinophilic infl ammation, namely interleukin (IL)-13 for the recruitment and IL-5 for the activation and life prolongation of the eosinophils, has been shown to be triggered by fungal antigens in patients with chronic rhinosinusitis [8]. This immune response was independent from the presence or absence of any detectable IgE-mediated allergy, and in striking contrast to its absence in healthy controls [8,9]. Whereas many different species can be recovered from chronic rhinosinusitis patients as well as healthy individuals, only Alternaria species have been shown to consistently induce the immune responses characteristic for chronic rhinosinusitis, which in turn are responsible for the recruitment (IL-13) and activation (IL-5) of eosinophils [8].…”
mentioning
confidence: 99%